Narrativas biográficas de Dandara Aragão: práticas educativas informais, prostituição e o uso de droga no bordel do centro da cidade de Fortaleza - Matos, Camila Saraiva de (2016)
The scope of this work is to understand the informal educational practices and teaching and learning processes developed by former prostitute inside a brothel located in the center of Fortaleza entitled Gata Garota and in the Narcotics Anonymous group – N. A.. In view of this, I emphasize the importance of making visible the life story of a sex worker, Dandara Aragão. As interlocutions transferred by her can make a more elaborate perception of everyday life in the red-light area, allowing for the identification of educational praxis that occur in cited whorehouse and emerges as a builder of space knowledge. I emphasize that the speech of biographed yield discussions that go beyond educational practices, given that the problems of drug addiction and addiction are also present throughout the research. Therefore, I emphasize the importance of biographical narrative in this study. It is through the discursive productions that seek to better understand the processes that encompass the tone of prostitution, knowing the routine of a prostitute and inferring certain questions, such as: the relationship between the practice of prostitution and drug use. I emphasize that, when working with narratives, some aspects should be taken into account, as the fact that the subject, to report events experienced by him often to the rebuilds, giving new meaning to them and presenting a new interpretation. So the narrative is not a point true because the informant when reestablishes his ideas for the story, you can reconstruct experience, with a new understanding and a new perspective. The use of narrative involves memories and forgetfulness, showing the use of memory. The memory is not constituted solely by the subject, but is embedded in a social context, family, political and historical. The memory is a mechanism made in this through experience or experiences that occurred in a past, selected and transformed into speech. In this research, the narrative, together with the memory, are treated through open interviews. Interviews propose a methodological action, using as a basis the qualitative research model. A memory and narratives reveal, selectively, the tracks and trials experienced by sex worker. Filtering which can be remembered and what should be forgotten. Consequently, the biographical approach provides visibility to the trajectories of a being, featuring its history and individuality which, translated into words, intertwine the different areas and configure themes as debated by society, such as prostitution and drug use. Thus, I seek to this study highlight life chronicled as a central point for the construction of knowledge, showing the many possibilities of knowing the experience of the other and thus acquire knowledge with her. Then, highlight the multiple facets that underlie the professional figure of Dandara sex: a literacy teacher, and dance the godmother of Narcotics Anonymous groups. Featuring thus the underworld as a space that also conceives educational practices.